The Influence of Transparency and Accountability in Zakat Management on Muzakki's Interest at Baznas, Lumajang Regency - Urmila, Titin; Suswati Risnaeni, Umi; Farid, Muhammad; Munawaroh, Silvia (Journal of Islamic Contemporary Accounting and Business, 2024)
The interest of Muzakki is one of the perspectives used by zakat managers to determine a person's willingness to give zakat on their wealth to a zakat institution. The factors influencing Muzakki's interest in paying zakat are accountability and transparency. In performing zakat payments, it is not uncommon for a Muzakki to choose a zakat payment through an institution recommended by the government, one that is trustworthy in fulfilling its responsibilities, and easily accessible for accurate and sufficient information in every activity. The purpose of this study is to determine the effect of transparency and accountability on zakat management at Baznas, Lumajang Regency. The method used in this study is a quantitative approach. The data collection method was done by sampling due to time, energy, and cost limitations. The analysis method used is quantitative analysis, which is a tool that uses calculations to determine the extent of the influence between variables. The results of this study show a positive and significant effect of the transparency variable on the interest of Muzakki at Baznas, Lumajang Regency. There is also a positive and significant effect of the accountability variable on the interest of Muzakki at Baznas, Lumajang Regency.